Absorbable tissue repair membrane as well as preparation method and application thereof
By adopting a multi-layer superposition architecture, the resorbable tissue repair membrane and the combination of absorbable metal and natural silk fibroin biofilm is solved in the prior art, the problems of metal non-degradable, acidic degradation products causing inflammation and hygroscopic softening, and tissue repair effect without secondary surgery is achieved.
Patent Information
- Application Number
- CN202411788843.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-25
AI Technical Summary
The presence of non-degradable metal materials in clinical applications of existing tissue repair membranes leads to the need for secondary surgery, the acidic degradation products of polymers trigger inflammation, high hygroscopic softening and lack the ability to maintain bone graft space.
The absorbable tissue repair membrane is adopted with a multi-layer superposition architecture. The intermediate layer structure is an absorbable metal and the outer layer structure is a biofilm. The biofilm is made of natural silk fibroin and is equipped with drugs or repair factors through a carrier to promote bone formation and induce osteocyte differentiation.
It provides isolation and support during tissue wound healing, and can be metabolized by the human body after healing, without secondary surgery, has strong biocompatibleness, and the degradation products do not cause immune response, effectively improving the healing speed and effect of bone wounds.
Smart Images

Figure CN119868646A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an absorbable tissue repair membrane and a preparation method and application thereof, belonging to the technical field of tissue repair. Background Art
[0002] Bone defect is a common clinical disease. Through surgical procedures, a membrane is placed between soft tissue and bone defect to establish a biological barrier, thereby creating a relatively closed bone regeneration environment, selectively blocking fibroblasts and epithelial cells with faster migration speed from entering the bone defect area, and at the same time, it is a biocompatible material that does not hinder the natural healing of the wound. Tissue repair membranes are widely used in medical treatments such as dental implants, maxillofacial surgery, cesarean section, and neurosurgery. They can cover the wound surface, avoid infection, and stimulate local tissue growth.
[0003] According to the different degradation characteristics of the barrier membrane, the current tissue repair membrane materials are mainly divided into metal, high molecular polymer, and collagen biomaterials. The material of metal tissue repair membrane is mainly titanium alloy. This repair membrane can provide good support effect, but titanium is not degradable and needs secondary surgery to remove it later. At the same time, it is accompanied by a very high probability of exposure to oral soft tissue after surgery, which limits the further application of this product. The polymer tissue repair membrane has good mechanical properties and excellent biodegradability. The degradation products can be degraded by the blood and eventually form water and carbon dioxide to be excreted from the body, but its acidic degradation products will reduce the local pH value and easily cause oral inflammation. Degradable collagen tissue repair membranes can be degraded in the body, without the need for secondary surgery to remove them, and the degradation products will not cause the body's immune response. However, this type of repair membrane often absorbs moisture and softens during clinical use and adsorbs on the defect area. It lacks the ability to maintain bone graft space, thus failing to achieve the ideal bone augmentation effect. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an absorbable tissue repair membrane and its preparation method and application, which can play an isolating and supporting role during tissue wound healing, and can be metabolized by the human body after the wound is healed, without the need for secondary surgery to remove it, and has strong biocompatibility.
[0005] To achieve the above object, the present invention is implemented by adopting the following technical solutions: In a first aspect, the present invention provides an absorbable tissue repair membrane, wherein the absorbable tissue repair membrane is a multi-layer stacked structure, which includes an intermediate layer structure and an outer layer structure; The material of the intermediate layer structure is absorbable metal, and the absorbable metal is used to provide strength support for the absorbable tissue repair membrane; The outer layer structure is arranged on the upper and lower surfaces of the middle layer structure, and is a biofilm of one or more layers. The biofilm is used to promote tissue repair and prevent the tissue from being stimulated by metal stress.
[0006] Optionally, the intermediate layer structure is one of a porous structure, a metal wire woven structure, a metal frame structure or a membrane structure, and its thickness ranges from 10 to 500 μm.
[0007] Optionally, when the intermediate layer structure adopts a porous structure, the pore size range is 0.01~1mm.
[0008] Optionally, the absorbable metal includes a main metal and an alloy metal, wherein the main metal accounts for more than 80% of the total mass of the absorbable metal, the main metal is one of zinc, magnesium, and iron, and the alloy metal is one or more of magnesium, iron, copper, calcium, manganese, phosphorus, lithium, and silver.
[0009] Optionally, the biofilm is a membrane-like structure, the thickness of the membrane-like structure ranges from 1 to 30 μm, and the material thereof is natural silk fibroin.
[0010] Optionally, drugs or repair factors are carried by a carrier between the outer layer structure and the intermediate layer structure, and the carrier and the drugs or repair factors are mixed in the biomembrane. The drugs and repair factors are used to promote bone formation and induce osteocyte differentiation.
[0011] Optionally, the carrier includes one or more of polylactic acid-glycolic acid copolymer, sodium alginate, chitosan, and sodium hyaluronate, the drug includes simvastatin, and the repair factor includes one or more of bone morphogenetic protein-2 and insulin-like growth factor 2.
[0012] In a second aspect, the present invention further provides a method for preparing the absorbable tissue repair membrane described in any one of the above items, comprising: Obtaining absorbable metal by metal smelting, wherein metal elements in the absorbable metal are evenly distributed; The intermediate layer structure is prepared by using absorbable metal, and the structure is one of a porous structure, a metal wire woven structure, a metal frame structure or a membrane structure; preparing a silk fibroin solution, wherein the concentration of the silk fibroin solution is in the range of 4-15wt%; The upper and lower sides of the middle layer structure are dip-coated and dried or electrospun with a silk fibroin solution, and then freeze-dried to form an outer layer structure, thereby obtaining an absorbable tissue repair membrane.
[0013] Furthermore, it also includes loading drugs or repair factors, including: The carrier is mixed with the drug or repair factor, and dispersed evenly to obtain a mixed solution; immersing the absorbable tissue repair membrane in the mixed solution; The absorbable tissue repair membrane is taken out, blow-dried and solidified, and then vacuum-dried at 40-60° C. for 12-20 hours to obtain an absorbable tissue repair membrane loaded with drugs or repair factors.
[0014] In a third aspect, the present invention also provides an application of the absorbable tissue repair membrane described in any one of the above items, including use for tissue defect repair, wherein the tissue defects include periodontal guided bone tissue regeneration, dura mater repair, hernia patch and cesarean section repair, and the use of the absorbable tissue repair membrane includes one or more of bending shaping, trimming, and support shaping.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention is a multi-layer structure, wherein the outer layer is made of biofilm and the middle layer is made of absorbable metal. The outer biofilm has good biocompatibility, and the absorbable metal can play a supporting role during the healing of bone wounds. At the same time, the absorbable metal also has a certain osteogenesis effect, further achieving an ideal bone augmentation effect. The outer biofilm and the absorbable metal in the middle layer of the present invention are both degradable. The outer biofilm is washed first, and the absorbable metal in the middle layer is absorbed later. After the wound is healed, the biofilm and the absorbable metal can be completely metabolized by the human body after the blood circulation function is reconstructed in the human body, without the need for secondary surgery to remove them. The degradation products will not cause an immune response in the body. The biofilms on the upper and lower sides can greatly reduce the risk of wound exposure, overcoming all the shortcomings of non-degradable metal titanium films, high molecular polymer repair films, and collagen repair films. The biomembrane of the present invention adopts a silk fibroin membrane, which is safer in terms of immunogenicity and biocompatibility, and drugs or repair factors can be loaded through a carrier between the outer biomembrane and the middle absorbable metal layer, effectively improving the speed and effect of bone wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a SEM schematic diagram of the zinc alloy film in Example 1 of the present invention at a magnification of 20,000 times; Figure 2 This is a schematic diagram of the structure of the absorbable tissue repair membrane prepared in Example 1 of the present invention; Figure 3 This is a schematic diagram of the curved shaping structure of the absorbable tissue repair membrane prepared in Example 1 of the present invention; Figure 4 Schematic diagram of hard tissue sections under a microscope 10 of the absorbable tissue repair membrane of Example 1 of the present invention and the collagen membrane of Comparative Example 1 implanted in the mandibular defect area of a dog 16 weeks later, wherein a is a schematic diagram of the absorbable tissue repair membrane of Example 1, and b is a schematic diagram of the collagen membrane of Comparative Example 1; Figure 5It is a schematic diagram comparing the bone volume fraction (BV / TB) and the area-to-volume ratio of new bone (BS / BV) of the absorbable tissue repair membrane of Example 1 of the present invention and the collagen membrane of Comparative Example 1 implanted in the mandibular defect area of dogs for 16 weeks; Figure 6 The SEM schematic diagram of the cross section of the absorbable tissue repair membrane of Example 1 of the present invention and the collagen membrane of Comparative Example 1 after being implanted in the mandibular defect area of dogs for 4 weeks and the schematic diagram of the element surface distribution; Figure 7 Schematic diagram of wounds after the absorbable tissue repair membrane of Example 1 of the present invention and the pure titanium repair membrane of Comparative Example 2 were implanted in the mandibular defect area of a dog for 4 weeks, wherein a is a schematic diagram of the pure titanium repair membrane, and b is the absorbable tissue repair membrane of the embodiment; Figure 8 Schematic diagram of the absorbable tissue repair membrane prepared in Example 1 of the present invention being immersed in PLGA, sodium hyaluronate, chitosan, and sodium alginate respectively; Fig. 9 Schematic diagram of the surface state of the absorbable tissue repair membrane prepared in Example 1 of the present invention before and after loading drugs, wherein the carrier in a is PLGA, the carrier in b is sodium hyaluronate, the carrier in c is chitosan, the carrier in d is sodium alginate, and no drug is loaded in e; In the figure: 1-absorbable tissue repair membrane, 2-outer layer structure, 3-middle layer structure. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention. Example 1
[0018] An embodiment of the present invention provides an absorbable tissue repair membrane, and a preparation method thereof comprises the following steps: The first step is to prepare an intermediate layer structure. In this embodiment, the intermediate layer structure adopts a porous structure, and the material is a zinc-magnesium alloy, in which the mass of zinc accounts for 95% of the total weight.
[0019] The preparation process of the porous membrane includes: Metal magnesium and metal zinc are melted and mixed to obtain a uniformly distributed zinc-magnesium alloy. The zinc-magnesium alloy is then subjected to rough rolling, foil rolling and other operations to obtain a zinc-magnesium alloy film with a thickness of 30 μm. Its microstructure morphology is as follows Figure 1 As shown, it can be seen Figure 1 There are many white crystals in the figure, which are the second image of magnesium, which proves the uniform preparation of zinc-magnesium alloy film.
[0020] The zinc-magnesium alloy membrane is cleaned and polished, and then subjected to wire cutting, punching, sterilization and other operations to obtain an intermediate layer with a porous structure, namely, a porous membrane.
[0021] The principle of GBR repair technology is to form a relatively closed growth space at the affected area. Osteoblasts are less affected by the outside world in the closed space, especially because they can shield the rapid growth of soft tissue. The bone formation effect is often better. However, the barrier also hinders the transport of nutrients. Therefore, opening micropores of 0.01~1mm on the surface can shield the space-occupying effect of soft tissue eroding bone tissue, but will not isolate the mutual transport of nutrients and blood supply. Therefore, it is necessary to open holes in the metal membrane.
[0022] Step 2: Prepare silk fibroin solution: a. Weigh the silk, clean it and place it in a reactor with purified water at a ratio of 1g:50mL. Heat the reactor to boil the purified water. Add 1g of 1% sodium carbonate solution (100L:500g) for every 50mL of purified water to ensure that the silk is completely immersed in boiling water. Boil for 60 minutes and take out the silk to scrub. After each scrubbing, change the water and remove the surface sericin. Scrub with purified water for more than 3 times.
[0023] b. Repeat step a, immerse the silk completely in boiling water, boil it for 45 minutes, take it out, wash it with purified water for more than 3 times, and dry it in a forced air drying oven at 75°C to obtain degummed silk.
[0024] c. Prepare 9.3M lithium bromide solution (807.7g lithium bromide, add 2000mL purified water), add 9.3M lithium bromide solution into the reactor and heat to 70°C, put the degummed silk into the 9.3M lithium bromide solution and stir for 2 hours. The ratio of degummed silk to 9.3M lithium bromide solution is 15g:100mL, until the degummed silk is completely dissolved to obtain a silk solution.
[0025] d. After the silk solution is cooled to 30°C, it is divided into dialysis bags, placed in dialysis tanks, and then placed in a medical refrigerator. Set the dialysis temperature to 4°C. On the first day, the water in the dialysis tank is changed every 2 hours. Starting from the second day, the water in the dialysis tank is changed every 3 hours. The dialysis is continued for 3 days.
[0026] e. Freeze-dry the silk solution. After coating the plate, place the stainless steel mold in a freeze dryer for freeze drying. After freeze drying, remove the mold and obtain a silk fibroin film.
[0027] f. Dissolve the silk fibroin film in formic acid to obtain a silk fibroin solution.
[0028] Step 3: Prepare biofilm on both sides of the porous membrane This embodiment adopts a drying method, which specifically includes: coating the silk fibroin solution on the upper and lower sides of the porous membrane, drying at 55°C for 40 hours, and freeze-drying to form a silk fibroin membrane with a thickness of 18 μm, and finally obtaining an absorbable tissue repair membrane with a structure as shown in FIG. Figure 2 As shown, the middle layer is a porous membrane, and both the upper and lower sides are biofilms. Example 2
[0029] This embodiment provides an absorbable tissue repair membrane, and the preparation method thereof comprises the following steps:
[0030] The first step is to prepare an intermediate layer structure. In this embodiment, the intermediate layer structure adopts a metal wire woven structure, and the material is a magnesium-iron alloy, in which the mass of magnesium accounts for 90% of the total weight.
[0031] The second step is to prepare a silk fibroin solution, which is the same as in Example 1 and will not be described in detail here.
[0032] Step 3: Prepare biofilm on both sides of the porous membrane This embodiment adopts electrospinning, and the specific parameters include: injection pump flow rate 30mL / h, the distance range between the nozzle and the collector is 80mm, the temperature is 20°C, the humidity is 35%, and a silk fibroin film with a thickness of 25μm is formed on the upper and lower sides of the middle layer structure, and finally an absorbable tissue repair membrane is obtained. Example 3
[0033] The present embodiment provides an absorbable tissue repair membrane, and the preparation method thereof includes the following steps: the first step is to prepare an intermediate layer structure. In the present embodiment, the intermediate layer structure adopts a metal frame structure, and the material is an iron-manganese alloy, in which the mass of iron accounts for 85% of the total weight.
[0034] The second step is to prepare a silk fibroin solution, which is the same as in Example 1 and will not be described in detail here.
[0035] Step 3: Prepare biofilm on both sides of the porous membrane This embodiment adopts a drying method, specifically including: coating the silk fibroin solution on the upper and lower sides of the porous membrane, drying at 65°C for 36 hours, and freeze-drying to form a silk fibroin membrane with a thickness of 8 μm, and finally obtaining an absorbable tissue repair membrane. Example 4
[0036] On the basis of Example 1, this example carries drugs or repair factors on the absorbable tissue repair membrane, and the carrier is sodium hyaluronate, which specifically includes the following steps: Sodium hyaluronate and distilled water are mixed to prepare a sodium hyaluronate solution with a mass fraction of 8%.
[0037] Add drug simvastatin to the sodium hyaluronate solution, put it into a centrifuge tube, shake it at high speed until the high molecular polymer is completely dissolved, let it stand for 2 hours to eliminate bubbles, and obtain a drug solution.
[0038] The absorbable tissue repair membrane was placed in a centrifuge tube, and kept completely submerged, sonicated for 60 minutes and then allowed to stand for 2 hours.
[0039] The absorbable tissue repair membrane was taken out from the centrifuge tube, and dried and solidified with a hair dryer. During the drying and solidification process, the membrane had to be turned over on both sides. Then, an oven was used, the temperature was set to 50°C, and the vacuum was drawn for 16 hours to obtain the absorbable tissue repair membrane loaded with drugs.
[0040] In some embodiments, a spraying method may also be used, that is, a mixed solution of the carrier and the drug or the repair factor may be sprayed on both sides of the absorbable tissue repair membrane. Example 5
[0041] The difference between this embodiment and embodiment 4 is that the sodium hyaluronate solution is replaced by a chitosan solution, and the preparation method thereof comprises: Chitosan and distilled water were mixed to obtain a chitosan solution with a mass fraction of 1%. Example 6
[0042] The difference between this embodiment and embodiment 4 is that the sodium hyaluronate solution is replaced by a sodium alginate solution, and the preparation method thereof comprises: Sodium alginate and distilled water were mixed to obtain a sodium alginate solution with a mass fraction of 1%. Example 7
[0043] The difference between this embodiment and embodiment 4 is that the sodium hyaluronate solution is replaced by a polylactic acid-co-glycolic acid (PLGA) solution, and the preparation method thereof comprises: The polylactic acid-glycolic acid copolymer and tetrahydrofuran are mixed to obtain a polylactic acid-glycolic acid copolymer solution with a mass fraction of 8%.
[0044] Comparative Example 1: This comparative example provides a collagen membrane, which is a 30×40 absorbable biological membrane / periosteum produced by Bio-Gide of Switzerland.
[0045] Comparative Example 2: This comparative example provides a pure titanium repair membrane with a thickness of 30 μm, which is formed by femtosecond laser cutting and sterilized by irradiation.
[0046] The absorbable tissue repair membranes prepared in Examples 1 to 7, the collagen membrane of Comparative Example 1, and the pure titanium repair membrane of Comparative Example 2 were tested and analyzed for their performance.
[0047] Performance test 1: First, a canine mandibular defect model was prepared, and bone powder was filled in the defect area. The absorbable tissue repair membrane of Example 1 and the collagen membrane of Comparative Example 1 were implanted in the defect area, respectively. After 16 weeks, the bone tissue in the defect area was taken out to make hard tissue sections stained with toluidine blue, and the sections were placed under a microscope at 10 times to observe the regeneration of bone tissue. The absorbable tissue repair membrane was used as follows: Figure 3 As shown, the absorbable tissue repair membrane can be bent and shaped in the bone defect area, and can be trimmed arbitrarily according to the bone defect area.
[0048] The results are as follows Figure 4 As shown, Figure 4 a is the absorbable tissue repair membrane of Example 1, Figure 4 b is the collagen membrane of comparative example 1. It can be seen that the new bone in the collagen membrane is limited to the surrounding of the original host bone (at the green arrow), and the oral mucosal fibrous tissue can be seen growing into the defect area. This is because the collagen membrane's own support performance is insufficient, resulting in a weakened barrier effect, which causes bone powder to leak out and soft tissues such as the oral mucosa to grow in, thus affecting the regeneration of bone tissue. In addition to achieving new bone regeneration on the surface of the host bone, the absorbable tissue repair membrane of Example 1 also shows new bone distributed in a dotted manner in the defect area (at the red arrow). This part of the new bone is different from the bone regenerated by bone cells on the surface of the host bone, but is formed by osteoblasts adsorbed on the surface of the bone powder. This effectively illustrates that the absorbable tissue repair membrane of Example 1 has a good barrier effect and can provide a good spatial basis for the migration and regeneration of bone cells.
[0049] Furthermore, by observing the coronal plane, it can be seen that the absorbable tissue repair membrane retains more bone powder in the defect area, while the collagen membrane loses bone powder. By observing the horizontal and sagittal planes, it can be seen that a large amount of new bone is formed on the alveolar ridge side of the defect area of the absorbable tissue repair membrane. The new bone is full in shape and integrated with the bone powder, while a small amount of new bone is formed by the collagen membrane. Moreover, due to the loss of bone powder, the bone density and quality are significantly less than that of the absorbable tissue repair membrane.
[0050] Therefore, it can be seen that the absorbable tissue repair membrane of Example 1 can play a good isolation barrier role and promote bone tissue regeneration due to the support of the absorbable metal in the middle layer.
[0051] Performance Test 2: A defect area of 20*10*2mm was selected as the ROI, and the new bone mass score in the ROI was calculated using the ZZKS-MicroCT4.1 software in the micro-CT (ZKKS-MCT-Sharp, KaishengMedical, China) equipment. Three parallel samples were collected in each group, and the differences in data between groups were analyzed by one-way ANOVA.
[0052] The bone volume fraction (BV / TB) and the area-to-volume ratio (BS / BV) of the absorbable tissue repair membrane of Example 1 and the collagen membrane of Comparative Example 1 are compared. Figure 5 As shown, it can be seen that the bone mass fraction and the area-to-volume ratio parameters of the absorbable tissue repair membrane of Example 1 are better than those of Comparative Example 1, indicating that Example 1 can achieve an ideal bone augmentation effect.
[0053] Performance Test 3: The corrosion of the absorbable tissue repair membrane of Example 1 was studied and the element surface distribution was analyzed. The experimental steps and the repeated parts of the above experimental steps are not repeated here. The only difference is that the middle layer of the membrane material, i.e. the zinc-magnesium alloy membrane, was taken out four weeks after implantation, and the cross-section of the membrane material was observed at 1000 by scanning electron microscopy, and the composition was analyzed by EDS.
[0054] The results are as follows Figure 6 As shown, the film material suffers from both uniform corrosion and non-uniform corrosion in the dog's body. After four weeks, the degradation depth is about 20~30μm, and the products of zinc alloy degradation are zinc, oxygen and calcium, which are safe and harmless to the human body.
[0055] Performance Test 4: A canine mandibular defect model was prepared, and bone powder was filled in the defect area. The absorbable tissue repair membrane of Example 1 and the pure titanium repair membrane of Comparative Example 2 were implanted in the defect area, and photos of the defect area were taken three weeks after implantation. Figure 7 As shown, Figure 7 a is a photo of the pure titanium repair film. Figure 7 b is a photo of the absorbable tissue repair membrane. By comparing the two, it can be seen that the pure titanium repair membrane was exposed in the oral soft tissue and the soft tissue was torn after the implantation surgery, while the wound of the absorbable tissue repair membrane was intact, and the metal titanium was non-degradable, and a second surgery was required to remove it later. This effectively illustrates that the biological membrane of the outer structure of the absorbable tissue repair membrane is well compatible with the soft tissue at the wound, has good biocompatibility, and both the outer layer and the middle layer can be absorbed and degraded, without the need for a second surgery to remove it.
[0056] Performance Test Five: The performance of the drug-loaded absorbable tissue repair membranes prepared in Examples 4 to 7 is analyzed below.
[0057] First, the absorbable tissue repair membrane is immersed in sodium hyaluronate, chitosan, sodium alginate and polylactic acid-co-glycolic acid as shown in FIG. Figure 8 As shown, from Figure 8It can be seen that the solvent effects of each group of solution systems are ideal, all of which are clear, transparent and stable liquids, without large agglomerations or sedimentation; compared with polylactic acid-glycolic acid copolymer, the other three natural polymer solutions have a higher viscosity, similar to the state of liquid glue.
[0058] Next, the absorbable tissue repair membranes loaded with drugs prepared in Examples 2 to 5 were placed under an ultra-depth microscope to observe the surface state and cross-section conditions. Fig. 9 As shown, Fig. 9 e is the surface state of the absorbable tissue repair membrane without being immersed in any solution. By comparison, the four carriers of sodium hyaluronate, chitosan, sodium alginate and polylactic acid-glycolic acid copolymer are all immersed in the surface micropores, and the solutions block the pores evenly, with the blocking rates greater than 90%.
[0059] Then, the absorbable tissue repair membrane was weighed before and after dipping, and the results are shown in Table 1.
[0060] Table 1: Weight of absorbable tissue repair membranes of Examples 4 to 7 before and after dipping
[0061] As can be seen from Table 1, since PLGA has the highest concentration, its coating weight is the largest, followed by chitosan, and there is no significant difference in the coating weights of sodium alginate and sodium hyaluronate.
[0062] In summary, the absorbable tissue repair membrane can achieve good loading for all four dip-coating systems.
[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An absorbable tissue repair membrane, characterized in that: The absorbable tissue repair membrane is a multi-layer stacked structure, which includes an intermediate layer structure and an outer layer structure; The material of the intermediate layer structure is absorbable metal, and the absorbable metal is used to provide strength support for the absorbable tissue repair membrane; The outer layer structure is arranged on the upper and lower surfaces of the middle layer structure, and is a biofilm of one or more layers. The biofilm is used to promote tissue repair and prevent the tissue from being stimulated by metal stress.
2. The absorbable tissue repair membrane according to claim 1, characterized in that: The intermediate layer structure is one of a porous structure, a metal wire braided structure, a metal frame structure or a membrane structure, and its thickness ranges from 10 to 500 μm.
3. The absorbable tissue repair membrane according to claim 2, characterized in that: When the intermediate layer structure adopts a porous structure, the pore size range is 0.01-1 mm.
4. The absorbable tissue repair membrane according to claim 1, characterized in that: The absorbable metal includes a main metal and an alloy metal, wherein the main metal accounts for more than 80% of the total mass of the absorbable metal, the main metal is one of zinc, magnesium, and iron, and the alloy metal is one or more of magnesium, iron, copper, calcium, manganese, phosphorus, lithium, and silver.
5. The absorbable tissue repair membrane according to claim 1, characterized in that: The biofilm is a membrane-like structure, the thickness of the membrane-like structure ranges from 1 to 30 μm, and the material of the membrane-like structure is natural silk fibroin.
6. The absorbable tissue repair membrane according to claim 1, characterized in that: Drugs or repair factors are carried by carriers between the outer layer structure and the middle layer structure. The carriers and drugs or repair factors are mixed in the biofilm. The drugs and repair factors are used to promote bone formation and induce osteocyte differentiation.
7. The absorbable tissue repair membrane according to claim 6, characterized in that: The carrier includes one or more of polylactic acid-glycolic acid copolymer, sodium alginate, chitosan, and sodium hyaluronate; the drug includes simvastatin; and the repair factor includes one or more of bone morphogenetic protein-2 and insulin-like growth factor 2.
8. A method for preparing the absorbable tissue repair membrane according to any one of claims 1 to 7, characterized in that: include: Obtaining absorbable metal by metal smelting, wherein metal elements in the absorbable metal are evenly distributed; The intermediate layer structure is prepared by using absorbable metal, and the structure is one of a porous structure, a metal wire woven structure, a metal frame structure or a membrane structure; preparing a silk fibroin solution, wherein the concentration of the silk fibroin solution is in the range of 4-15wt%; The upper and lower sides of the middle layer structure are dip-coated and dried or electrospun with a silk fibroin solution, and then freeze-dried to form an outer layer structure, thereby obtaining an absorbable tissue repair membrane.
9. The method for preparing the absorbable tissue repair membrane according to claim 8, characterized in that: It also includes loading drugs or repair factors, including: The carrier is mixed with the drug or repair factor, and dispersed evenly to obtain a mixed solution; immersing the absorbable tissue repair membrane in the mixed solution; The absorbable tissue repair membrane is taken out, blow-dried and solidified, and then vacuum-dried at 40-60° C. for 12-20 hours to obtain an absorbable tissue repair membrane loaded with drugs or repair factors.
10. A use of the absorbable tissue repair membrane according to any one of claims 1 to 7, characterized in that: The invention is used for repairing tissue defects, including periodontal guided bone tissue regeneration, dura mater repair, hernia patch and cesarean section repair. The absorbable tissue repair membrane is used in one or more ways including bending shaping, trimming and supporting shaping.